2020
DOI: 10.2337/db19-0432
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Derived From Schwann Cells Ameliorate Peripheral Neuropathy in Type 2 Diabetic Mice

Abstract: Schwann cell-derived exosomes communicate with dorsal root ganglia (DRG) neurons. The current study investigated the therapeutic effect of exosomes derived from healthy Schwann cells (SC-Exos) on diabetic peripheral neuropathy (DPN). We found that intravenous administration of SC-Exos to type 2 diabetic db/db mice with peripheral neuropathy remarkably ameliorated DPN by improving sciatic nerve conduction velocity and increasing thermal and mechanical sensitivity. These functional improvements were associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
111
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 96 publications
(114 citation statements)
references
References 50 publications
3
111
0
Order By: Relevance
“…In a preclinical study, Lopez-Verrilli et al reported that Schwann cell-derived exosomes were internalized by DRG axons to promote axonal regeneration (123). Our group showed that exosomes derived from Schwann cells (SC-exos) increased intraepidermal nerve fiber density in the footpad and reduced axonal and myelin damage of the sciatic nerve, leading to a reduction of neuropathic symptoms in DN mice (124). In contrast, exosomes derived from Schwann cells cultured in highglucose medium facilitated the development of DN by reducing epidermal nerve fibers (125).…”
Section: Extracellular Mirnas In Peripheral Neurovascular Functionmentioning
confidence: 86%
“…In a preclinical study, Lopez-Verrilli et al reported that Schwann cell-derived exosomes were internalized by DRG axons to promote axonal regeneration (123). Our group showed that exosomes derived from Schwann cells (SC-exos) increased intraepidermal nerve fiber density in the footpad and reduced axonal and myelin damage of the sciatic nerve, leading to a reduction of neuropathic symptoms in DN mice (124). In contrast, exosomes derived from Schwann cells cultured in highglucose medium facilitated the development of DN by reducing epidermal nerve fibers (125).…”
Section: Extracellular Mirnas In Peripheral Neurovascular Functionmentioning
confidence: 86%
“…Exosomes derived from healthy Schwann cells (SC-Exos) show therapeutic effects for type 2 diabetic peripheral neuropathy by improving sciatic nerve conduction velocity and increasing thermal and mechanical sensitivity. Western blot analysis of sciatic nerve tissues showed that the DPN considerably increased Sema6A expression, whereas the SC-Exos treatment, significantly reduced Sema6A expression, suggesting that Sema6A could contribute to DPN [112].…”
Section: Semaphorins In Diabetic Neuropathymentioning
confidence: 96%
“…Nrp1, Nrp2 [108,109] Sema3A Not mentioned [110,111] Sema6A Not mentioned [112] Diabetic wound healing Sema4D PlexinB2 [113] Sema6A Not mentioned [114] Diabetic osteoporosis Sema3A Not mentioned [115][116][117][118]…”
Section: Sema3cmentioning
confidence: 99%
“…Exosomes can be produced by the vast majority of cells with different origins and numerous functions. The cells from which exosomes are secreted include T cells [73,74], platelets [75], megakaryocytes [76] mast cells [77,78], neurons [79,80], oligodendrocytes [81] and Schwann cells [82][83][84][85]. Similarly, cells with stemness properties, such as mesenchymal stromal cells (MSCs) [86][87][88] and induced pluripotent stem cells (iPSCs) [89,90], have been reported to release exosomes.…”
Section: Different Types and Functions Of Cells That Release Exosomesmentioning
confidence: 99%